Elimination of a cholecystokinin receptor agonist 'trigger' in an effort to develop positive allosteric modulators without intrinsic agonist activity. Issue 9 (1st May 2015) - Desai, Aditya J.; Henke, Brad R.; Miller, Laurence J.
Graphical abstract